Do Earnings, Debt Decisions, Dividends Policy, and Size Affect Firm Value? Evidence from the Property and Real Estate Sector - Salsabila, Syahla Aulia; Simon, Zainal Zawir (SAN Scientific, 2025)
The objective of this study is to assess the impact of Price Earning Ratio (PER), Debt to Equity Ratio (DER), Dividend Payout Ratio (DPR), and Firm Size on Firm Value in the Property and Real Estate Sector listed on the Indonesia Stock Exchange. The research was conducted on a population of 79 companies with a sample size of 15, using purposive sampling. Secondary data from the Indonesian Stock Exchange website and the companies' websites was utilized for the study. The research employed panel data regression as the method. The findings suggest that PER, DER, and DPR have no significant impact on firm value. In contrast, firm size negatively and significantly affects firm value. When considered together, all independent variables significantly affect firm value. The managerial implications of this research highlight the importance of comprehending the relationship between PER, DER, DPR, and Firm size on Firm value, providing crucial strategic insights for managers to enhance the firm's appeal to investors by demonstrating the potential for higher profit growth.